How Green is the Economic Complexity in the Central and Eastern European Union Countries? - Neagu, Olimpia; Neagu, Mădălin-Ioan; Gavurova, Beata (Frontiers in Environmental Science, 2022)
The paper analyses the association between economic complexity and openness to trade green products in eleven Central and Eastern European Union (EU) countries over the period of 2003-2016. The study uses the ”green openness index” as it is framed by the Beta Akademi Social Science Lab in order to explain the progress in the productive structure of the European economies. In a panel data approach comprising of eleven EU economies, other explanatory variables of economic complexity are included: financial development, research and development (R&D) expenditures, and number of patents. The methodological approach includes: testing cross-sectional dependence of considered variable and second generation test for stationarity check. Cointegration on long run is verified by Westerlund test and estimation of regression coefficients uses FMOLS and DOLS models. Finally the causality relationship between economic complexity and explanatory variables is tested with Dumitrescu-Hurlin test. Empirical results show that Economic Complexity Index (ECI) is positively associated with green openness index (GOP), financial development, R&D expenditures and number of patents in the examined panel of countries. A validated causality relationship is running from green trade to economic complexity and from economic complexity to financial development and number of patents. It is also revealed validated bidirectional causality between R&D expenditures and ECI. Policy implications are also provided.